INHERITED DISORDERS OF AMINO ACID METABOLISM: BIOCHEMICAL FOUNDATIONS AND MOLECULAR MECHANISMS - Mahmudova Madina Rasuljon qizi; Shukurlayeva Mehriniso Xayrullo qizi (TADQIQOTLAR, 2025)
Abstract Background: Inborn errors of amino acid metabolism constitute a significant class of genetic disorders that may lead to severe neurological impairment, growth retardation, and systemic dysfunction if not diagnosed and managed promptly. Methods: A comprehensive literature review was conducted, examining epidemiological data, biochemical mechanisms, diagnostic strategies, and therapeutic approaches related to major inherited amino acid metabolism disorders. Results: Conditions such as phenylketonuria, maple-syrup urine disease, and homocystinuria exhibit distinct biochemical signatures enabling early detection through newborn screening. Tandem mass spectrometry has substantially improved diagnostic precision. Therapeutic strategies primarily include dietary restriction, cofactor supplementation, and metabolic detoxification, while emerging modalities— such as gene therapy and enzyme replacement—demonstrate promising potential. Conclusion: Early identification via systematic newborn screening, combined with targeted dietary and pharmacological management, significantly enhances long- term outcomes. Future research is directed toward molecularly targeted therapies, including gene-editing techniques and small-molecule modulators.